The Boundaries of the Capital Gap in Poland - Prędkiewicz, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper seeks to identify the limits of the funding gap in relation to equity capital in Poland. The following thesis was proposed: companies operating in Poland have difficulty obtaining equity capital from VC funds and business angel investors in the 1 million PLN to 15 million PLN range. An analysis is done on 36 VC funds and business angel preferences in Poland, confirming that the thesis is true. Further aims of the article are to: 1) put definitions related to the financial gap in order, 2) analyse the VC market in Poland, particularly in terms of investment limits and stage business financing, 3) analyse the business angel market in Poland.